The story of Tobit: a comparative literary analysis - Toloni, Giancarlo (Journal for the study of Judaism, 2023)
This volume charts Tobit’s narrative sources in myth, legend and folktale through comparative literary analysis, firmly placing the story in the genre of the didactic and edifying religious novel